The Quality Characteristics of Different Wheat Varieties Grown Under Varying Sowing Dates in Two Locations in the Northern State in Sudan - Hassan, Hayat A; Hussien, Abdel Rahim H. A. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This research was conducted to study the effect of different sowing dates on the quality characteristics of wheat (Triticum aestivum L.) grown in two soil types and to identify varieties that could perform relatively well underdelayed sowing conditions. Six released Sudanese wheat varieties were chosen, namely, El Nilein, Wadi Elneel, Giza 168, Debeira, Sasaraibe and Condor which grown in Northern State at Selaim Basin (19º.11'N, 30º.31'E) and Dongola Research Station Farm (DRSF, 19º.08'N, 30º.27'E). The crops were sown in stratified sowing dates from 1st November up to 10th January with 14 days interval. The first location, Dongola Research Station Farm (DRSF), represented the high terrace soils, whereas the second, Selaim basin, represented the alluvial soils. Split-plot design was used, sowing dates in the main plots and varieties in the sub-plots. The six sowing dates (SD1 to SD6) were grouped to early (1th Nov (SD1) –15th Nov (SD2.), normal (29th Nov. (SD3) -13rd Dec. (SD4) and late (27th Dec.(SD5)–10th Jan. (SD6). At harvest, samples were taken from each plot and analyzed qualitatively. Characters such ashectoliter weight (test weight or grain density) and 1000 kernel weight showed maximum values in the fourth sowing date (13th Nov.) and minimum values in the late sowing dates (27th Dec. and10th Jan.) in the two locations. In Selaim, El Nilein and Debeira were found significantly higher in hectoliter and 1000 kernel weights (831.57g/Land47.83); (827.9g/L and 40.00g, respectively), compared to the other varieties. Moisture contents for the whole meal and extracted flour, for all the varieties, in the two locations were found to be ranged from 5.90 to 6.60% and from 10.80 to 12.52%, respectively. All the results obtained for moisture were found to be within the Sudanese StandardsSpecifications (SDS 036/2013 and SDS 037/2014). Protein and gluten (wet and dry) contents improved by delayed sowing date. Debeira and El Nelein proved to be superior for protein and gluten contents in both Selaim and DRSF locations.